Spain : Selected Issues-Labor Market Polices and Unemployment Dynamics. (IMF Staff Country Reports; Country Report, 1996)
This Selected Issues paper analyzes labor market policies and unemployment dynamics in Spain. It provides a brief overview of economic developments and the institutional evolution of the Spanish labor market. The paper presents a basic model of the labor market, which is estimated for 1971-93. The regression results establish the basic underlying relationships among employment, labor force participation, and real wages. They also illustrate the importance of lags in the econometric specification and allow the identification of key structural changes in the labor market.